Development of Consumer Behavior Model, Customer Satisfaction as a Mediator of LPG Gas Customer Loyalty - Wilang Ana Putri Wilang Ana Putri; Wisnalmawati Wisnalmawati (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2026)
The number of retail agents of PT. Watu Langit has declined over recent years, partly due to regulatory violations committed by several LPG retailers, which resulted in the termination of cooperation agreements and subsequently affected customer loyalty. In this context, this study aims to examine whether price determination, LPG product availability, and service recovery influence customer loyalty, with customer satisfaction positioned as a mediating variable. The study surveyed customers from several LPG retail stores, including Toko Anugrah, Toko Rejo Abadi, Toko TB Gemilang, Toko Slamet, and Toko Mili, yielding a total of 137 respondents selected through purposive sampling. The findings indicate that price determination, product availability, and service recovery significantly influence customer loyalty. Furthermore, customer satisfaction mediates the effects of product availability and service recovery on loyalty, although it does not mediate the relationship between price determination and customer loyalty. By positioning customer satisfaction as a mediating mechanism, this study contributes to consumer behavior literature by clarifying the process through which operational and service-related factors shape loyalty outcomes. Practically, the findings offer insights for retail managers in designing pricing strategies, maintaining product availability, and implementing effective service recovery practices to enhance customer satisfaction and strengthen long-term loyalty.